ANALISIS PERBAIKAN SISTEM PENTANAHAN PADA KAKI MENARA SALURAN TRANSMISI TEGANGAN TINGGI 150 KV BANTUL-SEMANU JOGJAKARTA - Suyanto, Muhammad (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2007)
The research was carried out to get information about the improvement of gro-unding resistant value in tower feet of-high-voltage network, 150 kV, along tower trans-mission in power station, Bantul, Semanu. A good grounding system is used to flow cur-rent into the ground and prevent the current flow into the electrical equipment if electrical fault occurs. The result of measurement has shown that ground, type grumosol has a low grounding resistant value <10 Î© because its ground texture of clay has high ability to absorb and keep water and has very tiny particles and colloid property. The grounding resistant values of type regusol, litusol, brown latosol and red mediteran are above 20 Î© because of their ground texture, sand and clay. Chemical and physical reaction will take places in soil with clay structure. Its colloid property can tie/hold ion or water and sometimes free salt. The aim of this research is to get information about resistant value of soil type with almost â‰¤ 5 Î© by installing grounding electrode made from four galvanis steel coated with bronze with 15 mm in diameter, 10 meter long and two ground rods are parallel connected with 2 m each electrode and use counterpoise grounding system model. The result of the improvement is expected to meet standard requirement, SPLN almost â‰¤ 5 Î©.